An Implementation of a Computerized Cognitive Behavioral Treatment Program to Address Student Mental Health Needs: A Pilot Study in an After-School Program. (January 2019) - Sanders, Sara; Lane, Jessica J.; Losinski, Mickey; Nelson, Jessica; Asiri, Abdullah; Holloway, Samantha M. K.; Rogers, Elizabeth
This study evaluated the feasibility and effectiveness of an abbreviated computerized cognitive behavioral therapy (CCBT) software program, Camp Cope-A-Lot, in an after-school setting for elementary students identified as at risk for anxiety and other behavioral problems. Analysis of data from a small sample of students randomly assigned to a treatment or control group suggests that CCBT programs may ease the internalizing symptoms of students. We discuss limitations and implications for practitioners and future research.